PENGARUH MEDIA TANAM TOPSOIL DAN ABU JANJANG SAWIT TERHADAP PERTUMBUHAN BIBIT SENGON (Paraserianthes falcataria) - Budiyoko Budiyoko; Eny Dwi Pujawati; Sulaiman Bakri (Jurnal Sylva Scienteae, 2020)
The research aimed to know the effect of growing media that giving the best respons to growth of sengon and to know the effect of treathment the best for each parameter on the growth of sengon seedlings. The study was conducted duringjuni until Agustus 2016 in UPTD PembibitanTanamanHutanDinasKehutanan dan perkebunanKabupatenKotawaringin Timur Procinsi Kalimantan Tengah. Experiment design arranged in a Completely Randomized Design (RAL) with 6 treatment by 10 times. The treathment this study was combinasi from growing media with oil palm bunc by K (100 % Top Soil : 0 % AJS), A (90 % Top Soil : 10 % AJS), B (80 % Top Soil : 20 % AJS), C (70 % Top Soil : 30 % AJS), D (60 % Top Soil : 40 % AJS), dan E (50 % Top Soil : 50 % AJS). The research variable is percent of life tree, high tree, number of lieves, and diameter stem after that Data analysis using analysis of varian (Anova).Analysis results shows that giving oil palm buncis effect to percent of life tree, high tree, number of lieves, and diameter stem. Combinasitreathment of growing media C,D and E getting the best does to percent of life tree, as well as combination of growing media the effective to respon growth sengon is combination D for growthofhigt tree, and combinasi of growing media E for number of lieves and diameter stem.Keywords: Sengon; growing media and oil palm bunc